Development of the Distance Earth-Moon - Gimsa, Andreas (International Journal of Scientific Research and Management (IJSRM), 2020)
The expansion of the universe has a much larger dimension than previously thought. Because of entropy constancy, all masses must fall and all distances must increase. This is investigated using the example of the development of the distance Earth-Moon. The influence of tidal friction on the increase in distance is investigated and quantified. It was found that tidal friction exerts less influence than is currently assumed. If the influence of expansion and tidal friction is taken into account, a very good agreement between the calculations made here and the measured distance is achieved.